Pharmacological activation of PPARβ/δ preserves mitochondrial respiratory function in ischemia/reperfusion via stimulation of fatty acid oxidation-linked respiration and PGC-1α/NRF-1 signaling - Papatheodorou, Ioanna; Makrecka-Kuka, Marina; Kuka, Janis; Liepinsh, Edgars; Dambrova, Maija; Lazou, Antigone (Frontiers in Endocrinology, 2022)
Myocardial ischemia/reperfusion (I/R) injury leads to significant impairment of cardiac function and remains the leading cause of morbidity and mortality worldwide. Activation of peroxisome proliferator-activated receptor β/δ (PPARβ/δ) confers cardioprotection via pleiotropic effects including antioxidant and anti-inflammatory actions; however, the underlying mechanisms are not yet fully elucidated. The aim of this study was to investigate the effect of PPARβ/δ activation on myocardial mitochondrial respiratory function and link this effect with cardioprotection after ischemia/reperfusion (I/R). For this purpose, rats were treated with the PPARβ/δ agonist GW0742 and/or antagonist GSK0660 in vivo. Mitochondrial respiration and ROS production rates were determined using high-resolution fluororespirometry. Activation of PPARβ/δ did not alter mitochondrial respiratory function in the healthy heart, however, inhibition of PPARβ/δ reduced fatty acid oxidation (FAO) and complex II-linked mitochondrial respiration and shifted the substrate dependence away from succinate-related energy production and towards NADH. Activation of PPARβ/δ reduced mitochondrial stress during in vitro anoxia/reoxygenation. Furthermore, it preserved FAO-dependent mitochondrial respiration and lowered ROS production at oxidative phosphorylation (OXPHOS)-dependent state during ex vivo I/R. PPARβ/δ activation was also followed by increased mRNA expression of components of FAO -linked respiration and of transcription factors governing mitochondrial homeostasis (carnitine palmitoyl transferase 1b and 2-CPT-1b and CPT-2, electron transfer flavoprotein dehydrogenase -ETFDH, peroxisome proliferator-activated receptor gamma co-activator 1 alpha- PGC-1α and nuclear respiratory factor 1-NRF-1). In conclusion, activation of PPARβ/δ stimulated both FAO-linked respiration and PGC-1α/ NRF -1 signaling and preserved mitochondrial respiratory function during I/R. These effects are associated with reduced infarct size.